Resource-based framework for assessing cooperative institutional’s global competitiveness as small medium enterprise (SME) - Rismayani, R.; Wahyuningtyas, R.; Disastra, G. M. (Linguistics and Culture Review, 2021)
Indonesian business environment heavily influenced by small-medium enterprise (SME). In embracing Industry 4.0, Indonesian SME must be able to adapt the changing environment and competitive landscape. However, the concept of competitive advantages of SMEs, especially when concerning digital transformation, yet to be clearly defined and evaluated within the industry. Several factors, directly or indirectly, affect and jointly determine the competitive strength of an individual firm. The challenge is to properly identify the specific factors, and how and to what extent they affect firm SME competitiveness. Thus, emerge the necessity to study, understand, and then identify those factors. This research seeks to answer the challenge by using a qualitative approach and the resource-based framework. Six variables discovered through studying state-of-the-art literature, namely Digital Capability, Digital Orientation, Digital Innovation, Resistance, and Government Support that connected with SME Competitiveness. The link between variables were clarified. Resulting in proposal of how those variables entwined with each other. All variables were found to be directly related to Competitiveness, with some of the relations were moderated by Digital Innovation.